Perilaku Konsumtif Produk Kosmetik ditinjau dari Konsep Diri pada Mahasiswi - Khoiriyah, Siti Febiyanti; Hakim, Zun Azizul (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2021)
The aim of this research is to explore the impact of self concept on cosmetic consumtif behavior in female students. This exploration utilizes quantitative strategies with causal comparative approach. Participant of this study consist of 118 female undergraduate students. The hypothesis was analized using regression technique, with SPSS. The results of this study indicate the value of the regression coefficient of r = -0.323 with a significant level of 0.008 (p <0.05) meaning that there is a significant influence of self-concept on consumptive behavior, in a negative direction. This result means that the higher the self-concept owned by the female student, the lower the consumptive behavior of purchasing cosmetics. This study recommends efforts to get good self-concept to reduce consumptive behavior.